Digital Signal Processing 101 : Everything You Need to Know to Get Started - Parker, Michael, 1963- (Newnes is an imprint of Elsevier, 2017)
Digital Signal Processing 101: Everything You Need to Know to Get Started provides a basic tutorial on digital signal processing (DSP). Beginning with discussions of numerical representation and complex numbers and exponentials, it goes on to explain difficult concepts such as sampling, aliasing, imaginary numbers, and frequency response. It does so using easy-to-understand examples with minimum mathematics. In addition, there is an overview of the DSP functions and implementation used in several DSP-intensive fields or applications, from error correction to CDMA mobile communication to airborne radar systems. This book has been updated to include the latest developments in Digital Signal Processing, and hasïÅ½eight new chapters on: Automotive Radar Signal Processing Space-Time Adaptive Processing RadarField Orientated Motor Control Matrix Inversion algorithms GPUs for computing Machine LearningEntropy and Predictive CodingVideo compression.